Differential expression of cancer stem cell markers and pro-inflammatory cytokine IL-1β in the oral squamous cell carcinoma and oral submucosal fibrosis - Awasthi, Shriddha; Ahmad, Sharique; Gupta, Rahul; Iqbal, Mohammed Shariq; Ahmad, Ausaf (International Journal of Health Sciences, 2023)
Objectives: The poor prognosis of oral squamous cell carcinoma (OSCC) is vastly due to late diagnosis. The oral submucosal fibrosis (OSMF) is often unnoticed pathology linked with high risk of malignancy. Recently, we demonstrated that the clinicopathological alterations in OSMF and OSCC patients were correlated with cancer stem cell (CSCs) markers (CD133 and CD44). However, the parallel alterations of interleukin-1 beta (IL-1β) with CSCs expression are largely unexplored. Thus, we aimed to investigate the relationship between IL-1β alterations and CSC marker expression in both OSMF and OSCC situations. Methods: A total of 135 people have signed up for the study. There were sixty each in OSMF and OSCC groups, as well as 15 healthy controls. Levels of serum IL-1β were examined by ELISA. Immunohistochemistry (IHC) was used to examine the expression of CD133 and CD44. For evaluating differential CSCs expression, IHC scoring (0–4) was utilized. Results: The IHC results showed maximum subjects in the OSMF and OSCC displaying CD44 and CD133 positivity, although the extent of expression in terms of IHC scoring found variable. CD133 and CD44-positive subjects showed increased levels of IL-1β in the OSMF and OSCC group. Nevertheless, the enhancement of IL1β is more pronounced in the OSCC cases. Further, we observed a direct link of IL-1β levels with IHC scoring. Multivariate regression analysis demonstrated a significant role for CD44 and CD133 positivity in the increase of IL-1β levels. Conclusion: We concluded that concurrent simultaneous changes in CSC biomarkers and IL-1β may help with early detection of OSMF and OSCC conditions.